Canine olfaction as an alternative to analytical instruments for disease diagnosis: understanding 'dog personality' to achieve reproducible results. (9th January 2017) - Hackner, Klaus; Pleil, Joachim
Abstract: Recent literature has touted the use of canine olfaction as a diagnostic tool for identifying pre-clinical disease status, especially cancer and infection from biological media samples. Studies have shown a wide range of outcomes, ranging from almost perfect discrimination, all the way to essentially random results. This disparity is not likely to be a detection issue; dogs have been shown to have extremely sensitive noses as proven by their use for tracking, bomb detection and search and rescue. However, in contrast to analytical instruments, dogs are subject to boredom, fatigue, hunger and external distractions. These challenges are of particular importance in a clinical environment where task repetition is prized, but not as entertaining for a dog as chasing odours outdoors. The question addressed here is how to exploit the intrinsic sensitivity and simplicity of having a dog simply sniff out disease, in the face of variability in behavior and response.